Strategic Political Communication and Propaganda: Gibran RakabumingRaka’s Message Formulation in the 2024 Vice Presidential Campaign - Mutiara, Mutiara; Nastain , M (Universitas Telkom, 2025)
Gibran Rakabuming Raka's nomination as vice president in the 2024 election has invited pros and cons. Strong propaganda in the formulation of messages given by Gibran has received much attention from the public, as seen in the news on the internet and social media. So the victory of Gibran and his partner is interesting to study. This study aims to determine the formulation of messages in strong propaganda carried out by Gibran in the political campaign in the 2024 election. This research method uses a qualitative method on secondary data obtained from various sources, such as journals, survey or research results, news portals, books, reports, and other data sources. Secondary data collection is done through the documentation method. The theory used is the theory of message formulation by Alan H Monroe (1930)